A Study Of Labour Turnover And Organisational Productivity In The Cable Industry Of Nigeria Manufacturing Sector - Oginni, Babalola Oluwayemi; Omoyele, Samuel Olufemi (Advances in Social Sciences Research Journal, 2018)
The paper focused on the role of labour turnover in organisational productivity in the manufacturing sector with reference to cable industry in Lagos, Nigeria with a view to identifying causes of labour turnover and factors in productivity level; elements of organisational policies; and assess challenges confronting the variables. The study provides a framework to explain factors responsible for labour turnover with its implications on organisational productivity as it was found in the cable manufacturing sector of Nigerian economy which has not been previously investigated by scholars. A survey design was adopted, 5 cable organisations were purposively chosen through a preliminary survey of the cable organisations in the three senatorial districts of Lagos State. A sample of 420 employees was chosen from 650 employees representing 65% response rate. The administered questionnaire was designed in line 5 Likert rating scales. It was found that employees’ decision to leave and join another organisation is a constant phenomenon in the world of work which is contingent on many variables such as work design, emotional trauma, location and organisational politics emanating from organisational policies etc. and the result also showed that there is a significant relationship between labour turnover and productivity level of organisation at 0.05 level of sig. It showed that work factors, environmental factors, personal factors as well as organisational policies factors are the basic components of labour turnover with degree of influence on the organisational productivity.